2021
DOI: 10.1038/s41598-021-92034-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and utilization of lactic acid bacteria from silage in a warm and humid climate area

Abstract: The study aimed to isolate and identify lactic acid bacteria (LAB) from silages and their application to improve the fermentation quality of alfalfa. Forty-nine LAB strains were isolated from silages, and two strains were screened for growth and acid production rates. Then two strains were selected for Physiological and morphological tests and 16S rRNA sequencing. They were Gram-positive and Catalase-negative and were able to grow at pH 3.5 and at 45 °C, were unable to grow different NaCl concentrations as 3.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Homofermentatives LAB tended to be unable to maintain silage quality in aerobic conditions (Borreani et al 2018;Wilkinson and Davies 2013;Peng et al 2021). Some studies showed that although homofermentative LAB was more beneficial in anaerobic conditions, heterofermentative LAB actually increased the stability of silage quality in aerobic conditions (Muck et al 2018;Peng et al 2021). The present study proved that local LAB from local rice paddy was closest to L. plantarum's ability to encourage LAB populations in TMR silage.…”
Section: Microbial Composition Of Tmr Silagementioning
confidence: 47%
See 1 more Smart Citation
“…Homofermentatives LAB tended to be unable to maintain silage quality in aerobic conditions (Borreani et al 2018;Wilkinson and Davies 2013;Peng et al 2021). Some studies showed that although homofermentative LAB was more beneficial in anaerobic conditions, heterofermentative LAB actually increased the stability of silage quality in aerobic conditions (Muck et al 2018;Peng et al 2021). The present study proved that local LAB from local rice paddy was closest to L. plantarum's ability to encourage LAB populations in TMR silage.…”
Section: Microbial Composition Of Tmr Silagementioning
confidence: 47%
“…According to Ellis et al (2016), the most commonly used strains of LAB were L. plantarum and other Lactobacilli, and Enterococci (E. faecium) and some Pediococci. Homofermentatives LAB tended to be unable to maintain silage quality in aerobic conditions (Borreani et al 2018;Wilkinson and Davies 2013;Peng et al 2021). Some studies showed that although homofermentative LAB was more beneficial in anaerobic conditions, heterofermentative LAB actually increased the stability of silage quality in aerobic conditions (Muck et al 2018;Peng et al 2021).…”
Section: Microbial Composition Of Tmr Silagementioning
confidence: 99%
“…Further studies of microbial community structure and composition are necessary. Our previous study showed that L. rhamnosus produces acid and grows rapidly ( Peng et al, 2021 ). In this study, no obvious separation of LR combined with a low corn flour ratio (0, 3, and 6%) was observed, which may be due to various factors, such as the high buffer energy and low WSC content of paper mulberry ( Dong et al, 2020 ; Guo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…After all strains were isolated and purified, their acid production and growth rate in 24 h were measured on MRS medium (anaerobic at 37°C) ( Peng et al, 2021 ). Lacticaseibacillus rhamnosus (LR) strain (BDy3-10), which had the highest acid production rate, and Lentilactobacillus buchneri (LB) strain (TSy1-3), which had the fastest growth rate, were selected as the LAB additives in this study ( Peng et al, 2021 ). As shown in the strain characteristics Supplementary Table 1 , two strains were Gram-positive and Catalase-negative.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation